Identification of infection by Chikungunya, Zika, and Dengue in an area of the Peruvian coast. Molecular diagnosis and clinical characteristics - Sánchez-Carbonel, José (2018)
Objective: To assess the presence of Dengue, Chikungunya, and Zika in serum samples of patients with acute febrile illness in Piura, Peru and describe the most common clinical features. Results: Dengue was the most common arbovirus detected in 170/496 (34.3%), followed by Zika in 39/496 (7.9%) and Chikungunya in 23/496 (4.6%). Among the 170 samples positive for Dengue, serotype 2 was the most predominant type present in 97/170 (57.1%) of samples, followed by the serotype 3 in 9/170 (5.3%). Headaches, muscle pain, and joint pain were the most common symptoms associated with fever in patients with Dengue and Zika. No symptoms predominance was observed in patients with Chikungunya.Dengue is considered the most frequent arbovirus in Peru and the number of cases has increased dramatically in the last 5 years. However, it is not the only arbovirus that circulates along the northern coast of Peru. It has also been determined the presence of Zika and Chikungunya in our population, which may suggest the circulation of other arboviruses that have not been detected.